Herpes simplex virus type 1 (HSV-1)-induced apoptosis in human dendritic cells as a result of downregulation of cellular FLICE-inhibitory protein and reduced expression of HSV-1 antiapoptotic latency-associated transcript sequences - Kather, Angela; Raftery, Martin J.; Devi-Rao, Gayathri; Lippmann, Juliane; Giese, Thomas; Sandri-Goldin, Rozanne M.; Schönrich, Günther (Journal of virology, 2010)
Herpes simplex virus type 1 (HSV-1) is one of the most frequent and successful human pathogens. It targets immature dendritic cells (iDCs) to interfere with the antiviral immune response. The mechanisms underlying apoptosis of HSV-1-infected iDCs are not fully understood. Previously, we have shown that HSV-1-induced apoptosis of iDCs is associated with downregulation of the cellular FLICE-inhibitory protein (c-FLIP), a potent inhibitor of caspase-8-mediated apoptosis. In this study, we prove that HSV-1 induces degradation of c-FLIP in a proteasome-independent manner. In addition, by using c-FLIP-specific small interfering RNA (siRNA) we show for the first time that downregulation of c-FLIP expression is sufficient to drive uninfected iDCs into apoptosis, underlining the importance of this molecule for iDC survival. Surprisingly, we also observed virus-induced c-FLIP downregulation in epithelial cells and many other cell types that do not undergo apoptosis after HSV-1 infection. Microarray analyses revealed that HSV-1-encoded latency-associated transcript (LAT) sequences, which can substitute for c-FLIP as an inhibitor of caspase-8-mediated apoptosis, are much less abundant in iDCs as compared to epithelial cells. Finally, iDCs infected with an HSV-1 LAT knockout mutant showed increased apoptosis when compared to iDCs infected with the corresponding wild-type HSV-1. Taken together, our results demonstrate that apoptosis of HSV-1-infected iDCs requires both c-FLIP downregulation and diminished expression of viral LAT.